Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmolb.2022.763248
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses of the Immunological and Prognostic Roles of an IQGAP3AR/let-7c-5p/IQGAP3 Axis in Different Types of Human Cancer

Abstract: IQ motif containing GTPase-activating protein 3 (IQGAP3) is a member of the Rho family of guanosine-5′-triphosphatases (GTPases). IQGAP3 plays a crucial part in the development and progression of several types of cancer. However, the prognostic, upstream-regulatory, and immunological roles of IQGAP3 in human cancer types are not known. We found that IQGAP3 expression was increased in different types of human cancer. The high expression of IQGAP3 was correlated with tumor stage, lymph node metastasis, and a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Its similar action has been reported in hepatocellular carcinoma, since sponging let-7c-5p has been associated with tumor proliferation and invasion [78]. In agreement with our results, let-7c-5p overexpression has been correlated with (i) a good prognosis in other gastrointestinal cancers, such as oesophageal carcinoma, as well as (ii) sensitivity to anticancer therapy [79]. Although hsa-let-7d-5p has not been studied so far in colorectal cancer drug response, its overexpression has been linked with sensitivity to tivantinib in breast cancer cell lines [80].…”
Section: Discussionsupporting
confidence: 90%
“…Its similar action has been reported in hepatocellular carcinoma, since sponging let-7c-5p has been associated with tumor proliferation and invasion [78]. In agreement with our results, let-7c-5p overexpression has been correlated with (i) a good prognosis in other gastrointestinal cancers, such as oesophageal carcinoma, as well as (ii) sensitivity to anticancer therapy [79]. Although hsa-let-7d-5p has not been studied so far in colorectal cancer drug response, its overexpression has been linked with sensitivity to tivantinib in breast cancer cell lines [80].…”
Section: Discussionsupporting
confidence: 90%
“…With 53 genome-wide associations, an intergenic TR seemed to have an impact on more than half of the top DEGs between HFP and LFP whole brains. The variant is located 2.7 kb downstream of the E3 ubiquitin ligase ENSGALG00000055092 (DCAF11) and 7.5 kb upstream of IQGAP3, which is required for proper cell cycle progression [76] and which influences immune cell infiltration and immune modulators [77]. A 294-bp intron deletion in RO60, a gene involved in the regulation of inflammatory gene expression [78], was associated with 30 DEGs, which might be responsible for the observation that 48.1% of DEGs between HFP and LFP belong to the PANTHER protein class defense/immunity (PC00090) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the expression of IQGAP3 is increased in highgrade serous ovarian cancer, and the proliferation, migration and invasion of ovarian cancer cell are inhibited when IQGAP3 is silenced [28] . Interestingly, high expression of IQGAP3 appears to be associated with tumor mutational burden, microsatellite instability, immune cell in ltration, and immunomodulatory agents, with integral roles in the progression and immune response of various human cancers [29] . IQGAP3 expression was negatively correlated with Dendritic cells resting, but positively correlated with B cells naive.…”
Section: Discussionmentioning
confidence: 99%